2012
DOI: 10.1007/s00253-012-3885-7
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis of d-glyceric acid by an alditol oxidase and directed evolution for enhanced oxidative activity towards glycerol

Abstract: Glycerol as a by-product of biodiesel production is an attractive precursor for producing d-glyceric acid. Here, we demonstrate the successful production of d-glyceric acid based on glycerol via glyceraldehyde in a two-step enzyme reaction with the FAD-dependent alditol oxidase from Streptomyces coelicolor A3(2). The hydrogen peroxide generated in the reaction can be used in detergent, food, and paper industry. In order to apply the alditol oxidase in industry, the enzyme was subjected to protein engineering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Glycerol ( S. coelicolor AldO enzyme reported a k cat = 17 s À1 and a k cat /K m = 1.2 9 10 4 M À1 s À1 for sorbitol, and values of k cat = 13 s À1 and k cat / K m = 4.1 9 10 4 M À1 s À1 for xylitol at pH 7.5 [17]; and a k cat /K m = 2.1 9 10 4 M À1 s À1 for glycerol at pH 9.0 [26]. Given the similar extents of oxidation of these different substrates by the OleT JE -HRV3C-AldO fusion enzyme (Table 2), it is likely that the kinetics of this fusion enzyme are similar to those reported previously.…”
Section: Enzyme Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…Glycerol ( S. coelicolor AldO enzyme reported a k cat = 17 s À1 and a k cat /K m = 1.2 9 10 4 M À1 s À1 for sorbitol, and values of k cat = 13 s À1 and k cat / K m = 4.1 9 10 4 M À1 s À1 for xylitol at pH 7.5 [17]; and a k cat /K m = 2.1 9 10 4 M À1 s À1 for glycerol at pH 9.0 [26]. Given the similar extents of oxidation of these different substrates by the OleT JE -HRV3C-AldO fusion enzyme (Table 2), it is likely that the kinetics of this fusion enzyme are similar to those reported previously.…”
Section: Enzyme Systemmentioning
confidence: 96%
“…This suggested that OleT JE can convert these hydroxylated fatty acids to further products (Figure 6). 0.5 ml reactions were set up with 5 µM OleT JE -HRV3C-AldO, 1% glycerol and 200 µM of either 2-OH or 3-OH myristic acid, or using 1 µM OleT JE /500 µM H 2 (27). Given the similar extents of oxidation of these different substrates by the OleT JE -HRV3C-AldO fusion enzyme ( Table 2), it is likely that the kinetics of this fusion enzyme are similar to those reported previously.…”
Section: Secondary Turnover Of 2-oh Myristic Acid and 3-oh Myristic Amentioning
confidence: 99%
“…The best alditol oxidase mutant for oxidation of glycerol was found to display a k cat value of only 0.06 s –1 . 44 …”
Section: Discussionmentioning
confidence: 99%
“…Glycerol is first oxidized with oxygen to glyceric acid via glyceraldehyde by the FAD-dependent alditol oxidase (Aldo)-catalyzed two-step oxidation reaction. [31][32][33] The substrate tolerance of the dihydroxy acid dehydratase (DHAD) in Sulfolobus solfataricus was reported recently. 16,34 Glyceric acid 10 produced from glycerol can be transformed into pyruvic acid and water without oxygen by the DHAD in S. solfataricus.…”
mentioning
confidence: 99%